Effect of Essential Oils on Growth Inhibition, Biofilm Formation and Membrane Integrity of Escherichia coli and Staphylococcus aureus (2021)
ABSTRACT: Biofilm as a cellular conformation confers survival properties to microbial populations and favors microbial resistance. Here, we investigated the antimicrobial, antibiofilm, antimotility, antihemolytic activity, and the interaction with synthetic membranes of 15 essential oils (EOs) on E. coli ATCC 25922 and S. aureus ATCC 29213. Antimicrobial activity of EOs was determined through microdilution method; development of the biofilm was assessed using the crystal violet assay and SEM microscopy. Results indicate that Lippia origanoides thymol–carvacrol II chemotype (LTC II) and Thymus vulgaris (TV) exhibited a significant antibacterial activity, with MIC values of 0.45 and 0.75 mg/mL, respectively. The percentage of biofilm formation inhibition was greater than 70% at subinhibitory concentrations (MIC50) for LTC II EO. The results demonstrate that these two oils had significantly reduced the hemolytic effect of S. aureus by 54% and 32%, respectively, and the mobility capacity by swimming in E. coli with percentages of decrease of 55% and 47%, respectively. The results show that LTC II and TV EOs can interact with the hydrophobic core of lipid bilayers and alter the physicochemical properties of membranes. The findings suggest that LTC II and TV oils may potentially be used to aid in the treatment of S. aureus and E. coli infections.